Three-proofing hardened coating for vehicle-mounted display and preparation method thereof

By adopting multi-layer coating structure and micro-concave coating technology on the explosion-proof film for on-board display, the problems of different clarity and low production efficiency of explosion-proof films in the prior art are solved, and the three-proof effects of anti-glare, anti-reflection and anti-fingerprint are achieved, and the adhesion ability and wear resistance are improved.

CN119505672APending Publication Date: 2025-02-25SICHUAN YUXI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411695846.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing explosion-proof film for on-board displays varies greatly at different angles. The CVD process production speed is slow and the equipment is expensive. It is difficult to produce continuously on a large scale. It is impossible to achieve three-preventive effects of anti-glare, anti-reflection and anti-fingerprint, which affects the user experience.

Method used

The three-anti-hardening coating consisting of a base material layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardening layer is adopted. Through micro-concave coating and ultraviolet curing technology, the three-anti-hardening effects of anti-glare, anti-reflection and anti-fingerprint are achieved, and the adhesion ability and wear resistance are improved.

Benefits of technology

It achieves consistency of picture clarity at different angles, improves the effects of anti-glare, anti-reflection and anti-fingerprint, enhances adhesion and wear resistance, and is suitable for applications in the field of high-end automotive screens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505672A_ABST
    Figure CN119505672A_ABST
Patent Text Reader

Abstract

The invention discloses a three-proofing hardened coating for vehicle-mounted display, which relates to the technical field of display coatings and sequentially comprises a base material layer, a prime coat AG layer, a high-refractive-index layer, a low-refractive-index layer and an anti-fingerprint hardened layer from bottom to top. According to the invention, the special phase difference film is adopted to design the explosion-proof film with a multi-layer structure for vehicle-mounted display in a wet coating manner, the explosion-proof film has the three-proofing effects of anti-dazzle, anti-reflection and anti-fingerprint, and meanwhile, the coating also has excellent adhesive ability and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of display coatings, and in particular to a three-proof hardened coating for vehicle-mounted displays and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, the car's internal screen, as a core component, is gradually becoming larger and more intelligent due to people's increasing requirements for display and touch effects. The reflection of the screen under the irradiation of external light and the refraction of the light from the internal luminous parts of the screen on the inside of the screen can easily cause glare and affect people's user experience. Therefore, in order to improve this defect and protect the screen, a layer of anti-glare (AG) explosion-proof film is generally applied to the surface of the screen. However, with the continuous changes in the market, a single anti-glare effect cannot meet the needs of customers. In addition to anti-glare, a high resolution of the display screen is also required. For this reason, the market uses sputtering or chemical vapor deposition (CVD) technology to deposit an anti-reflection layer (LR layer) on the original anti-glare film material. This method does achieve anti-reflection on the basis of anti-glare. However, with the rapid development of the new energy market, the large-screen and intelligent interior screens of automobiles, the CVD production process has slow production speed, expensive equipment, and difficulty in large-scale continuous production. These shortcomings restrict the development of explosion-proof films for vehicle displays. In addition, with the popularization of touch-screen displays, the anti-fingerprint effect of the screen is increasingly affecting the user experience, and the double anti-coating can no longer meet customer needs.

[0003] At present, the car screen protection film on the market generally adopts PET substrate, and the LR layer is deposited on the AG base coating by CVD process. The explosion-proof film for screen prepared by this method has undesirable problems: there are differences in the clarity of the picture at different angles; the LR layer is deposited on the AG particle layer by CVD process, and because of the unevenness of AG particles, there are differences in the deposition thickness, which easily leads to rainbow spots; conventional car display explosion-proof film only has anti-glare and anti-reflection or anti-glare and anti-fingerprint dual-proof film materials, and does not have the triple-proof effects of anti-glare, anti-reflection and anti-fingerprint, which limits its application in the field of high-end car screens; CVD process single-chip deposition production has low working efficiency and difficulty in continuous production. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a three-proof hardened coating for vehicle-mounted display and a preparation method thereof, the coating has three-proof effects of anti-glare, anti-reflection and anti-fingerprint, and also has excellent adhesion ability and wear resistance.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a three-proof hardened coating for vehicle-mounted display is provided, which comprises, from bottom to top, a substrate layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardened layer;

[0006] The substrate layer is one of a triacetyl cellulose film and a super-complex refractive film;

[0007] The primer AG layer is made of the following raw materials in parts by weight: 20-30 parts of in-situ polymerized functionalized matte polyurethane resin, 1-5 parts of photoinitiator I, 1-5 parts of thermal initiator I and 60-78 parts of solvent I;

[0008] The high refractive index layer is made of the following raw materials in parts by weight: 10-20 parts of oxylated bisphenol A diacrylate, 1-5 parts of photoinitiator II, 1-5 parts of thermal initiator II and 70-88 parts of solvent II;

[0009] The low refractive index layer is made of the following raw materials in parts by weight: 10-20 parts of pentaerythritol tetraacrylate, 1-5 parts of photoinitiator III, 1-5 parts of thermal initiator III and 37-84 parts of solvent III;

[0010] The anti-fingerprint hardening layer is made of the following raw materials in parts by weight: 20-30 parts of dual-solid organic resin, 1-5 parts of photoinitiator IV, 1-5 parts of thermal initiator IV, 0.5-1.5 parts of fluorine-containing auxiliary agent and 58.5-77.5 parts of solvent IV;

[0011] The in-situ polymerized functionalized matte polyurethane resin is prepared by the following steps:

[0012] (1) dispersing the hollow titanium dioxide in hydrogen peroxide, reflux in an oil bath at 75-85° C. for 3-5 hours, filtering, washing and drying to obtain hydroxylated hollow titanium dioxide; dispersing the hydroxylated hollow titanium dioxide in an ethanol solution, adding potassium persulfate to mix, then dropping methyl methacrylate (MMA), stirring at 75-85° C. for reaction for 3-5 hours, filtering, washing and drying to obtain hollow titanium dioxide@MMA;

[0013] (2) mixing isophorone diisocyanate (IPDI) and graft polymer diol, prepolymerizing at 75-85° C. for 2.5-3.5 hours, then adding dimethylol propionic acid (DMPA) and dibutyltin dilaurate (DBTDL) for 2.5-3.5 hours, and then adding 1,4-butanediol (BDO) for constant temperature reaction for 1-2 hours. After the NCO content in the reaction system is reduced to 50%, cooling and discharging the material, and storing it in the dark, a polyurethane (PU) prepolymer is obtained;

[0014] (3) The hollow titanium dioxide @MMA obtained in step (1), the polyurethane prepolymer obtained in step (2), an initiator and water are mixed, stirred at room temperature, then heated to 65-75° C., dibutyltin dilaurate (DBTDL) is added dropwise, and free radical polymerization is carried out for 3-5 hours. After the NCO content in the reaction system is reduced to 33%, the temperature is reduced, the material is discharged, and it is stored away from light to obtain an in-situ polymerized functionalized matte polyurethane resin.

[0015] Further, each layer is coated by micro-concave coating and dried at 90-100°C for 1-3 min and 300-500 mJ / cm 2 Curing is carried out by UV irradiation.

[0016] Furthermore, in step (1), the concentration of the ethanol solution is 1-3vt%; the mass ratio of hydroxylated hollow titanium dioxide to methyl methacrylate is 100:8-12, and the mass ratio of methyl methacrylate to potassium persulfate is 100:0.8-1.2.

[0017] Furthermore, in step (1), the hollow titanium dioxide particle size is 10-30 nm.

[0018] Further, in step (2), the grafted polymer diol is at least one of polycarbonate diol (PCDL), polybutylene adipate (PBA) and polyether diol (PPG-2000).

[0019] Furthermore, in step (2), the R value during the prepolymerization reaction is 2; the mass ratio of isophorone diisocyanate, dimethylolpropionic acid and 1,4-butanediol is 100:8-12:8-12; and the mass ratio of dimethylolpropionic acid and dibutyltin dilaurate is 100:0.4-0.6.

[0020] Furthermore, in step (3), the mass ratio of hollow titanium dioxide @MMA, polyurethane prepolymer and initiator is 13-17:100:4-6; the mass ratio of hollow titanium dioxide @MMA and dibutyltin dilaurate is 100:0.3-0.7.

[0021] Furthermore, in step (3), the initiator is azobisisobutyronitrile (AIBN).

[0022] Further, the substrate layer has a thickness of 40-125 μm;

[0023] The refractive index of the primer AG layer is 1.4-1.6, and the thickness is 2-5 μm;

[0024] The high refractive index layer has a refractive index of 1.60-1.65 and a thickness of 90-110 nm;

[0025] The low refractive index layer has a refractive index of 1.2-1.44 and a thickness of 90-110 nm;

[0026] The anti-fingerprint hardening layer has a refractive index of 1.2-1.44 and a thickness of 2-4 μm.

[0027] Furthermore, photoinitiator I, photoinitiator II, photoinitiator III and photoinitiator IV are each selected from one of BASF 1-hydroxy-cyclohexyl benzophenone (184), BASF 2-hydroxy-2-methyl-phenylpropionone-1 (1173), BASF liquid α-hydroxyketone composite photoinitiator (500) and BASF methyl benzoylformate (MBF).

[0028] Further, thermal initiator I, thermal initiator II, thermal initiator III and thermal initiator IV are each selected from one of Merck dibenzoyl peroxide (BPO) and Aladdin dilauroyl peroxide (LPO).

[0029] Furthermore, each of solvent I, solvent II, solvent III and solvent IV is selected from at least one of butanone, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate and butyl acetate.

[0030] Furthermore, the fluorine-containing auxiliary agent is one of Shin-Etsu KY1203, Dongye F8000, Daikin OPTOOLDAC-100UV and Taiyue Material HF234.

[0031] Furthermore, the oxylated bisphenol A diacrylate is diethoxy bisphenol A di(meth)acrylate.

[0032] Furthermore, the dual-solid organic resin is selected from aliphatic polyurethane acrylate containing -NCO group, which is one of UA VPLS2337, UA VP LS2396 and UA XP 2510.

[0033] The present invention has the following beneficial effects:

[0034] 1. The three-proof hardened coating for vehicle display of the present invention is composed of a substrate layer, a primer AG layer, a high folding layer, a low folding layer, and an anti-fingerprint hardened layer. The use of a triacetyl cellulose substrate (TAC) with a relatively small phase difference or a super-complex refractive film substrate (SRF) with a particularly large phase difference can reduce the mutual influence between the refracted light o light and the e light, and achieve clear image quality at different angles; by adding methacrylic acid modified nano inorganic particles to the primer AG layer, the anti-glare effect is improved under the condition of appropriate uniformity of the film surface haze; then a double-layer re-coating with different refractive indices is used to achieve the anti-reflection effect through the interference coherence principle; finally, a low surface energy anti-fingerprint layer is coated by a micro-concave wet coating method, and the anti-fingerprint layer is synergistically enhanced by a dual curing method of thermal curing and ultraviolet curing to achieve an anti-fingerprint effect.

[0035] 2. The present invention adopts a special phase difference film to design a 4-layer explosion-proof film for vehicle display by wet coating, which has the triple protection effects of anti-glare, anti-reflection and anti-fingerprint, and the haze is 5%-12%, which can be adjusted according to specific needs; the total light transmittance exceeds 95%, the visual reflectivity is less than 1%, the water contact angle is greater than 110°, and the hardness is greater than 2H-500. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the structure of the triple-proof hardened coating for vehicle-mounted display in Example 1. DETAILED DESCRIPTION

[0037] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0038] Example 1

[0039] A three-proof hardened coating for vehicle display, the structure of which is as follows Figure 1 As shown, from bottom to top, it includes a substrate layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardening layer;

[0040] The substrate layer is a triacetyl cellulose film with a thickness of 40-125 μm;

[0041] The primer AG layer is made of the following raw materials in parts by weight: 25 parts of in-situ polymerized functionalized matte polyurethane resin, 3 parts of BASF 2-hydroxy-2-methyl-phenylacetone-1 (1173), 2 parts of Merck dibenzoyl peroxide (BPO), 34.5 parts of propylene glycol methyl ether and 34.5 parts of methyl isobutyl ketone; the ... 2 Curing by ultraviolet light irradiation;

[0042] The high refractive index layer has a thickness of 100 nm and is made of the following raw materials in parts by weight: 12 parts of diethoxybisphenol A di(meth)acrylate, 3 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 2 parts of Merck dibenzoyl peroxide (BPO), 62.25 parts of methyl isobutyl ketone and 20.75 parts of butanone; it is coated by micro-concave coating, dried at 90°C for 1 min, and then 300 mJ / cm 2 Curing by ultraviolet light irradiation;

[0043] The low refractive index layer has a thickness of 100 nm and is made of the following raw materials in parts by weight: 20 parts of pentaerythritol tetraacrylate, 3 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 2 parts of Merck dibenzoyl peroxide (BPO), 2 parts of leveling agent BYK3700, 57 parts of propylene glycol methyl ether and 19 parts of butanone; a micro-concave coating method is adopted, and it is first dried at 90°C for 1 minute, and then 300 mJ / cm 2 Curing by ultraviolet light irradiation;

[0044] The anti-fingerprint hardening layer has a thickness of 3 μm and is made of the following raw materials in parts by weight: 30 parts of dual-solid organic resin (UA VPLS2337), 3 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 2 parts of Merck dibenzoyl peroxide (BPO), 1 part of fluorinated additive (KY1203), 55.5 parts of methyl isobutyl ketone and 18.5 parts of butanone; it adopts the micro-concave coating method, and is first dried at 100°C for 2 minutes, and then 500mJ / cm 2 Curing by ultraviolet light irradiation;

[0045] The in-situ polymerized functionalized matte polyurethane resin is prepared by the following steps:

[0046] (1) Ultrasonic dispersion of hollow titanium dioxide with a particle size of 20 nm in hydrogen peroxide, reflux in an oil bath at 80° C. for 4 h, filter, wash and dry to obtain hydroxylated hollow titanium dioxide; disperse the hydroxylated hollow titanium dioxide in a 2vt% ethanol solution, add potassium persulfate to mix, then drop methyl methacrylate (MMA), stir and react at 80° C. for 4 h, filter, wash and dry to obtain hollow titanium dioxide@MMA; wherein the mass ratio of hydroxylated hollow titanium dioxide to methyl methacrylate is 100:10, and the mass ratio of methyl methacrylate to potassium persulfate is 100:1;

[0047] (2) isophorone diisocyanate (IPDI) and polycarbonate diol (PCDL) are mixed, with an R value of 2, and prepolymerized at 80°C for 3 hours, then dimethylolpropionic acid (DMPA) and dibutyltin dilaurate (DBTDL) are added and reacted for 3 hours, and then 1,4-butanediol (BDO) is added and reacted at a constant temperature for 1.5 hours. After the NCO content in the reaction system is reduced to 50%, the temperature is reduced, the material is discharged, and the material is stored in the dark to obtain a polyurethane (PU) prepolymer; wherein the mass ratio of isophorone diisocyanate, dimethylolpropionic acid and 1,4-butanediol is 100:10:10; the mass ratio of dimethylolpropionic acid and dibutyltin dilaurate is 100:0.5;

[0048] (3) The hollow titanium dioxide @MMA obtained in step (1), the polyurethane prepolymer obtained in step (2), the initiator azobisisobutyronitrile (AIBN) and deionized water are mixed, ultrasonically stirred at room temperature for 30 minutes, then heated to 70°C, and dibutyltin dilaurate (DBTDL) is added dropwise through a constant pressure funnel within 30 minutes. Free radical polymerization is carried out for 4 hours. After the NCO content in the reaction system is reduced to 33%, the temperature is reduced, the material is discharged, and it is protected from light to obtain an in-situ polymerized functionalized matte polyurethane resin; wherein the mass ratio of the hollow titanium dioxide @MMA, the polyurethane prepolymer and the initiator is 15:100:5; and the mass ratio of the hollow titanium dioxide @MMA and dibutyltin dilaurate is 100:0.5.

[0049] Example 2

[0050] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the substrate layer is a super-refractive film (SRF).

[0051] Example 3

[0052] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that in the step (1) of preparing the in-situ polymerized functionalized matte polyurethane resin, the mass ratio of hydroxylated hollow titanium dioxide and methyl methacrylate is 100:15.

[0053] Example 4

[0054] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that in the step (2) of preparing the in-situ polymerization functionalized matte polyurethane resin, the grafted polymer diol is not polycarbonate diol (PCDL) but polybutylene adipate (PBA).

[0055] Example 5

[0056] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that in the step (2) of preparing the in-situ polymerization functionalized matte polyurethane resin, the grafted polymer diol is not polycarbonate diol (PCDL) but polyether diol (PPG-2000).

[0057] Example 6

[0058] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that in the step (2) of preparing the in-situ polymerized functionalized matte polyurethane resin, the R value during the polymerization reaction is 2.5.

[0059] Example 7

[0060] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that in the step (3) of preparing the in-situ polymerization functionalized matte polyurethane resin, the mass ratio of hollow titanium dioxide @MMA, polyurethane prepolymer and initiator is 10:100:5.

[0061] Example 8

[0062] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the primer AG layer is 4 μm.

[0063] Example 9

[0064] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the high refractive index layer is 120 nm.

[0065] Example 10

[0066] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the low refractive index layer is 120 nm.

[0067] Embodiment 11

[0068] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the anti-fingerprint hardened layer has a thickness of 4 μm.

[0069] Example 12

[0070] A three-proof hardened coating for vehicle-mounted display, which is different from Example 1 in that the fluorine-containing auxiliary agent is Daikin OPTOOLDAC-100UV.

[0071] Example 13

[0072] A three-proof hardened coating for vehicle-mounted display, comprising, from bottom to top, a substrate layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardened layer;

[0073] The substrate layer is a triacetyl cellulose film with a thickness of 40 μm;

[0074] The primer AG layer is made of the following raw materials in parts by weight: 20 parts of in-situ polymerized functionalized matte polyurethane resin, 1 part of BASF 2-hydroxy-2-methyl-phenylacetone-1 (1173), 1 part of Merck dibenzoyl peroxide (BPO) and 60 parts of propylene glycol methyl ether; the ... 2 Curing by ultraviolet light irradiation;

[0075] The high refractive index layer has a thickness of 90 nm and is made of the following raw materials in parts by weight: 10 parts of diethoxybisphenol A di(meth)acrylate, 1 part of BASF 1-hydroxy-cyclohexyl benzophenone (184), 1 part of Merck dibenzoyl peroxide (BPO) and 70 parts of butanone; it is coated by micro-concave coating, dried at 90°C for 1 min, and then 300 mJ / cm 2 Curing by ultraviolet light irradiation;

[0076] The low refractive index layer has a thickness of 90 nm and is made of the following raw materials in parts by weight: 10 parts of pentaerythritol tetraacrylate, 1 part of BASF 1-hydroxy-cyclohexyl benzophenone (184), 1 part of Merck dibenzoyl peroxide (BPO), and 37 parts of propylene glycol methyl ether; the low refractive index layer is coated by micro-concave coating, and is first dried at 90°C for 1 minute, and then 300 mJ / cm 2 Curing by ultraviolet light irradiation;

[0077] The anti-fingerprint hardening layer has a thickness of 2 μm and is made of the following raw materials in parts by weight: 20 parts of dual-solid organic resin (UA VPLS2337), 1 part of BASF 1-hydroxy-cyclohexyl benzophenone (184), 1 part of Merck dibenzoyl peroxide (BPO), 0.5 parts of fluorinated additive (KY1203), and 58.5 parts of methyl isobutyl ketone; it adopts a micro-concave coating method, and is first dried at 90°C for 1 minute, and then 300 mJ / cm 2 Curing by ultraviolet light irradiation;

[0078] The in-situ polymerized functionalized matte polyurethane resin is prepared by the following steps:

[0079] (1) Ultrasonic dispersion of hollow titanium dioxide with a particle size of 10 nm in hydrogen peroxide, reflux in an oil bath at 75° C. for 3 h, filter, wash and dry to obtain hydroxylated hollow titanium dioxide; disperse the hydroxylated hollow titanium dioxide in a 1 vt% ethanol solution, add potassium persulfate to mix, then drop methyl methacrylate (MMA), stir and react at 75° C. for 3 h, filter, wash and dry to obtain hollow titanium dioxide@MMA; wherein the mass ratio of hydroxylated hollow titanium dioxide to methyl methacrylate is 100:8, and the mass ratio of methyl methacrylate to potassium persulfate is 100:0.8;

[0080] (2) isophorone diisocyanate (IPDI) and polycarbonate diol (PCDL) are mixed, with an R value of 1.5, and prepolymerized at 75°C for 2.5 hours, and then dimethylolpropionic acid (DMPA) and dibutyltin dilaurate (DBTDL) are added to react for 2.5 hours, and then 1,4-butanediol (BDO) is added to react at a constant temperature for 1 hour. After the NCO content in the reaction system is reduced to 50%, the temperature is reduced, the material is discharged, and the material is stored in the dark to obtain a polyurethane (PU) prepolymer; wherein the mass ratio of isophorone diisocyanate, dimethylolpropionic acid and 1,4-butanediol is 100:8:8; the mass ratio of dimethylolpropionic acid and dibutyltin dilaurate is 100:0.4;

[0081] (3) The hollow titanium dioxide @MMA obtained in step (1), the polyurethane prepolymer obtained in step (2), the initiator azobisisobutyronitrile (AIBN) and deionized water are mixed, ultrasonically stirred at room temperature for 30 minutes, then heated to 65°C, and dibutyltin dilaurate (DBTDL) is added dropwise through a constant pressure funnel within 30 minutes, and free radical polymerization is carried out for 3 hours. After the NCO content in the reaction system is reduced to 33%, the temperature is reduced, the material is discharged, and it is stored away from light to obtain an in-situ polymerized functionalized matte polyurethane resin; wherein the mass ratio of the hollow titanium dioxide @MMA, the polyurethane prepolymer and the initiator is 13:100:4; the mass ratio of the hollow titanium dioxide @MMA and dibutyltin dilaurate is 100:0.3.

[0082] Embodiment 14

[0083] A three-proof hardened coating for vehicle-mounted display, comprising, from bottom to top, a substrate layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardened layer;

[0084] The substrate layer is a triacetyl cellulose film with a thickness of 125 μm;

[0085] The primer AG layer is made of the following raw materials in parts by weight: 30 parts of in-situ polymerized functionalized matte polyurethane resin, 5 parts of BASF 2-hydroxy-2-methyl-phenylacetone-1 (1173), 5 parts of Merck dibenzoyl peroxide (BPO) and 78 parts of propylene glycol methyl ether; the ...; the primer AG layer is made of the following raw materials in parts by weight; the primer AG layer is made of the following raw materials in parts by weight; the primer AG layer is made of the following raw materials in parts by weight; the 2 Curing by ultraviolet light irradiation;

[0086] The high refractive index layer has a thickness of 110 nm and is made of the following raw materials in parts by weight: 20 parts of diethoxybisphenol A di(meth)acrylate, 5 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 5 parts of Merck dibenzoyl peroxide (BPO) and 88 parts of butanone; it is coated by micro-concave coating, dried at 100°C for 3 minutes, and then 500 mJ / cm 2 Curing by ultraviolet light irradiation;

[0087] The low refractive index layer has a thickness of 110 nm and is made of the following raw materials in parts by weight: 20 parts of pentaerythritol tetraacrylate, 5 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 5 parts of Merck dibenzoyl peroxide (BPO), and 84 parts of propylene glycol methyl ether; the low refractive index layer is coated by micro-concave coating, and is first dried at 100° C. for 3 minutes, and then 500 mJ / cm 2 Curing by ultraviolet light irradiation;

[0088] The anti-fingerprint hardening layer has a thickness of 4 μm and is made of the following raw materials by weight: 30 parts of dual-solid organic resin (UA VPLS2337), 5 parts of BASF 1-hydroxy-cyclohexyl benzophenone (184), 5 parts of Merck dibenzoyl peroxide (BPO), 0.7 parts of fluorine-containing additive (KY1203), and 77.5 parts of methyl isobutyl ketone; it adopts a micro-concave coating method, and is first dried at 100°C for 3 minutes, and then 500mJ / cm 2 Curing by ultraviolet light irradiation;

[0089] The in-situ polymerized functionalized matte polyurethane resin is prepared by the following steps:

[0090] (1) Ultrasonic dispersion of hollow titanium dioxide with a particle size of 15 nm in hydrogen peroxide, reflux in an oil bath at 85° C. for 5 h, filter, wash and dry to obtain hydroxylated hollow titanium dioxide; disperse the hydroxylated hollow titanium dioxide in a 3vt% ethanol solution, add potassium persulfate to mix, then drop methyl methacrylate (MMA), stir and react at 85° C. for 5 h, filter, wash and dry to obtain hollow titanium dioxide@MMA; wherein the mass ratio of hydroxylated hollow titanium dioxide to methyl methacrylate is 100:12, and the mass ratio of methyl methacrylate to potassium persulfate is 100:1.2;

[0091] (2) isophorone diisocyanate (IPDI) and polycarbonate diol (PCDL) are mixed, with an R value of 2.5, and prepolymerized at 85°C for 3.5 hours, and then dimethylolpropionic acid (DMPA) and dibutyltin dilaurate (DBTDL) are added to react for 3.5 hours, and then 1,4-butanediol (BDO) is added to react at a constant temperature for 2 hours. After the NCO content in the reaction system is reduced to 50%, the temperature is reduced, the material is discharged, and the material is stored in the dark to obtain a polyurethane (PU) prepolymer; wherein the mass ratio of isophorone diisocyanate, dimethylolpropionic acid and 1,4-butanediol is 100:12:12; the mass ratio of dimethylolpropionic acid and dibutyltin dilaurate is 100:0.6;

[0092] (3) The hollow titanium dioxide @MMA obtained in step (1), the polyurethane prepolymer obtained in step (2), the initiator azobisisobutyronitrile (AIBN) and deionized water are mixed, ultrasonically stirred at room temperature for 30 minutes, then heated to 75°C, and dibutyltin dilaurate (DBTDL) is added dropwise through a constant pressure funnel within 30 minutes. Free radical polymerization is carried out for 5 hours. After the NCO content in the reaction system is reduced to 33%, the temperature is reduced, the material is discharged, and it is stored away from light to obtain an in-situ polymerized functionalized matte polyurethane resin; wherein the mass ratio of the hollow titanium dioxide @MMA, the polyurethane prepolymer and the initiator is 17:100:6; the mass ratio of the hollow titanium dioxide @MMA and dibutyltin dilaurate is 100:0.7.

[0093] Comparative Example 1

[0094] A coating for vehicle-mounted display, which is different from Example 1 in that the substrate layer is a PET film.

[0095] Comparative Example 2

[0096] A coating for vehicle display, which is different from Example 1 in that, in the preparation of the in-situ polymerization functionalized matte polyurethane resin, step (1) of modifying the hollow titanium dioxide is not performed, and step (3) of hollow titanium dioxide@MMA is replaced by hollow titanium dioxide.

[0097] Comparative Example 3

[0098] A coating for vehicle-mounted display, which is different from Example 1 in that in the step (2) of preparing the in-situ polymerized functionalized matte polyurethane resin, the R value during the polymerization reaction is 1.

[0099] Comparative Example 4

[0100] A coating for vehicle display, which is different from Example 1 in that in the step (3) of preparing the in-situ polymerized functionalized matte polyurethane resin, the mass ratio of hollow titanium dioxide @MMA, polyurethane prepolymer and initiator is 20:100:5.

[0101] Comparative Example 5

[0102] A coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the primer AG layer is 1 μm.

[0103] Comparative Example 6

[0104] A coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the high refractive index layer is 1 μm.

[0105] Comparative Example 7

[0106] A coating for vehicle-mounted display, which is different from Example 1 in that the thickness of the low refractive index layer is 1 μm.

[0107] Comparative Example 8

[0108] A coating for vehicle-mounted display, which is different from Example 1 in that the anti-fingerprint hardening layer has a thickness of 1 μm.

[0109] Comparative Example 9

[0110] A coating for vehicle-mounted display, which is different from Example 1 in that it does not contain a high refractive index layer.

[0111] Comparative Example 10

[0112] A coating for vehicle-mounted display, which is different from Example 1 in that it does not contain a low refractive index layer.

[0113] Comparative Example 11

[0114] A coating for a vehicle-mounted display, which is different from the coating in Example 1 in that it does not contain an anti-fingerprint hardening layer.

[0115] Comparative Example 12

[0116] A coating for vehicle-mounted display, which is different from Example 1 in that no modified hollow titanium dioxide nanoparticles are added to the primer AG layer.

[0117] Test Example 1

[0118] The coatings of Examples 1-12 and Comparative Examples 1-12 were tested respectively. According to the standard of JIS K7105-1981 "Test Method for Optical Properties of Plastics", their transmittance and haze were tested; according to the standard of JIS K5400-1990 "Determination of Adhesion Performance of Powder Coatings", their pencil hardness was tested; according to the standard of GB 1720-1979 "Determination of Adhesion of Paint Films", HC adhesion was tested, where 100 / 100 represents no film peeling at all, and 90 / 100 represents 10% peeling; according to HG / T 4303-2012 "Determination of Abrasion Resistance of Surface Hardened Polyester Film", the abrasion resistance of the film was tested, using 0000# steel wool, 500gf / cm 2 The wear resistance of the film is determined by testing the limit of the number of times the film surface can be worn without scratches. The higher the number of times the film can be worn, the better the effect. According to the standard of GB / T 30693-2014 "Measurement of the contact angle of plastic film with water", the water contact angle of the film surface is tested. The higher the water contact angle, the better the hydrophobicity and the better the anti-fingerprint effect. The reflectivity of the film is tested using a Konica CM-3600A spectrophotometer. The lower the reflectivity, the brighter the surface is, and the system stray light is reduced. The test results of various performances of the coating are shown in Table 1.

[0119] Table 1 Test results of various properties of coatings

[0120]

[0121]

[0122] As can be seen from Table 1, the use of a triacetyl cellulose substrate (TAC) with a relatively small phase difference or a super-refraction film substrate (SRF) with a particularly large phase difference can reduce the mutual influence between the refracted light o light and the e light, and achieve clear image quality at different angles (such as Examples 1-2 and Comparative Example 1); then, the anti-glare effect is achieved by adding methacrylic acid-modified hollow nano inorganic particles to the primer AG layer (such as Examples 3 and 7, Comparative Examples 2, 4 and 12); in addition, the in-situ polymerization functionalized matte polyurethane resin of the primer AG layer has different R values. The larger the R value, the more fully the isocyanate reacts with the polyol, the longer the polyurethane molecular chain, the larger the molecular weight, the higher the haze, and the better the mechanical properties (such as Example 6 and Comparative Example 3). Not only does the R value affect the mechanical properties of the product, but the difference in synthetic raw materials also directly affects the ratio of hard segments to soft segments in the polyurethane structure. For example, it also affects the mechanical properties of the product (such as Examples 4 and 5); then, a recoat with different refractive indices is used to achieve an anti-reflection effect through the interference coherence principle, and the refractive index is changed by adjusting the coating thickness to satisfy that the product of the refractive index and the thickness of the coating is equal to an odd multiple of 1 / 4 of the incident wavelength, thereby achieving the maximum anti-reflection effect (such as Examples 8-11, Comparative Examples 5-11); finally, a low surface energy anti-fingerprint layer is applied by a micro-concave wet coating method, and is modified with a perfluoroalkyl acrylate polymer (surface tension 10mN / m) with a lower surface tension than water (surface tension 72mN / m), juice (surface tension 50mN / m) and oil (surface tension 30mN / m), and the anti-fingerprint layer is synergistically enhanced by a dual-curing method of thermal curing and UV curing to achieve an anti-fingerprint effect (such as Examples 11 and 12, Comparative Examples 8 and 11).

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A three-proof hardened coating for vehicle display, characterized in that: From bottom to top, it includes a substrate layer, a primer AG layer, a high refractive index layer, a low refractive index layer and an anti-fingerprint hardening layer; The substrate layer is one of a triacetyl cellulose film and a super-complex refractive film; The primer AG layer comprises the following raw materials in parts by weight: 20-30 parts of in-situ polymerized functionalized matte polyurethane resin, 1-5 parts of photoinitiator I, 1-5 parts of thermal initiator I and 60-78 parts of solvent I; The high refractive index layer is made of the following raw materials in parts by weight: 10-20 parts of oxylated bisphenol A diacrylate, 1-5 parts of photoinitiator II, 1-5 parts of thermal initiator II and 70-88 parts of solvent II; The low refractive index layer is made of the following raw materials in parts by weight: 10-20 parts of pentaerythritol tetraacrylate, 1-5 parts of photoinitiator III, 1-5 parts of thermal initiator III and 37-84 parts of solvent III; The anti-fingerprint hardening layer is made of the following raw materials in parts by weight: 20-30 parts of dual-solid organic resin, 1-5 parts of photoinitiator IV, 1-5 parts of thermal initiator IV, 0.5-1.5 parts of fluorine-containing auxiliary agent and 58.5-77.5 parts of solvent IV; The in-situ polymerized functionalized matte polyurethane resin is prepared by the following steps: (1) dispersing the hollow titanium dioxide in hydrogen peroxide, reflux in an oil bath at 75-85° C. for 3-5 hours, filtering, washing and drying to obtain hydroxylated hollow titanium dioxide; The hydroxylated hollow titanium dioxide is dispersed in an ethanol solution, potassium persulfate is added and mixed, and then methyl methacrylate is added dropwise, and the mixture is stirred at 75-85° C. for 3-5 hours, and then the hollow titanium dioxide@MMA is obtained by suction filtration, washing and drying. (2) mixing isophorone diisocyanate and graft polymer diol, prepolymerizing at 75-85° C. for 2.5-3.5 hours, then adding dimethylol propionic acid and dibutyltin dilaurate for 2.5-3.5 hours, then adding 1,4-butanediol for constant temperature reaction for 1-2 hours, and after the NCO content in the reaction system is reduced to 50%, cooling, discharging, and storing in the dark to obtain a polyurethane prepolymer; (3) The hollow titanium dioxide @MMA obtained in step (1), the polyurethane prepolymer obtained in step (2), an initiator and water are mixed, stirred at room temperature, then heated to 65-75° C., dibutyltin dilaurate is added dropwise, and free radical polymerization is carried out for 3-5 hours. After the NCO content in the reaction system is reduced to 33%, the temperature is reduced, the material is discharged, and it is stored away from light to obtain an in-situ polymerized functionalized matte polyurethane resin.

2. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: Each layer is coated with micro-concave coating and dried at 90-100℃ for 1-3min and 300-500mJ / cm 2 Curing is carried out by UV irradiation.

3. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: In step (1), the concentration of the ethanol solution is 1-3vt%; the mass ratio of the hydroxylated hollow titanium dioxide to methyl methacrylate is 100:8-12, and the mass ratio of the methyl methacrylate to potassium persulfate is 100:0.8-1.

2.

4. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: In step (2), the R value during the prepolymerization reaction is 2; the mass ratio of isophorone diisocyanate, dimethylolpropionic acid and 1,4-butanediol is 100:8-12:8-12; the mass ratio of dimethylolpropionic acid and dibutyltin dilaurate is 100:0.4-0.

6.

5. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: In step (3), the mass ratio of the hollow titanium dioxide @MMA, the polyurethane prepolymer and the initiator is 13-17:100:4-6; the mass ratio of the hollow titanium dioxide @MMA and dibutyltin dilaurate is 100:0.3-0.

7.

6. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: The thickness of the substrate layer is 40-125 μm; The base coating AG layer has a refractive index of 1.4-1.6 and a thickness of 2-5 μm; The high refractive index layer has a refractive index of 1.60-1.65 and a thickness of 90-110 nm; The low refractive index layer has a refractive index of 1.2-1.44 and a thickness of 90-110 nm; The anti-fingerprint hardening layer has a refractive index of 1.2-1.44 and a thickness of 2-4 μm.

7. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: The photoinitiator I, photoinitiator II, photoinitiator III and photoinitiator IV are each selected from one of BASF 1-hydroxy-cyclohexyl benzophenone, BASF 2-hydroxy-2-methyl-phenyl acetone-1, BASF liquid α-hydroxy ketone composite photoinitiator and BASF methyl benzoylformate.

8. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: The thermal initiator I, thermal initiator II, thermal initiator III and thermal initiator IV are each selected from one of Merck dibenzoyl peroxide and Aladdin dilauroyl peroxide.

9. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: The solvent I, solvent II, solvent III and solvent IV are each selected from at least one of butanone, methyl isobutyl ketone, propylene glycol methyl ether, propylene glycol methyl ether acetate and butyl acetate.

10. The three-proof hardened coating for vehicle-mounted display according to claim 1, characterized in that: The fluorine-containing auxiliary agent is one of Shin-Etsu KY1203, Dongye F8000, Daikin OPTOOLDAC-100UV and Taiyue Material HF234.

Citation Information

Patent Citations

  • High-weather-resistance optical thin film and preparation method thereof

    CN116144278A

  • Anti-reflection and anti-dazzle film and preparation method thereof

    CN116755186A